2020
DOI: 10.1016/j.ijid.2020.03.082
|View full text |Cite
|
Sign up to set email alerts
|

Different Plasmodium falciparum clearance times in two Malian villages following artesunate monotherapy

Abstract: Background: Artemisinin resistance described as increased parasite clearance time (PCT) is rare in Africa. More sensitive methods such as qPCR might better characterize the clearance phenotype in sub-Saharan Africa. Methods: PCT is explored in Mali using light microscopy and qPCR after artesunate for uncomplicated malaria. In two villages, patients were followed for 28 days. Blood smears and spots were collected respectively for microscopy and qPCR. Parasitemia slope half-life was calculated after microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Whilst repeated assessments of parasite density shortly after initiation of treatment provide the most conclusive evidence on (changes in) parasite responsiveness (16), alternative metrics are used to compare the early effects of antimalarials. These include the proportion of individuals with residual parasitemia by microscopy (17) or PCR (3,7) or the concentration of the histidine rich protein-2 parasite antigen (18). The current study, examining the kinetics of mRNA transcripts indicative of ring-stage parasitemia following treatment (10,19), explicitly does not aim to present this measure as a proxy for parasite clearance half-lives or direct evidence of reduced susceptibility of parasites to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst repeated assessments of parasite density shortly after initiation of treatment provide the most conclusive evidence on (changes in) parasite responsiveness (16), alternative metrics are used to compare the early effects of antimalarials. These include the proportion of individuals with residual parasitemia by microscopy (17) or PCR (3,7) or the concentration of the histidine rich protein-2 parasite antigen (18). The current study, examining the kinetics of mRNA transcripts indicative of ring-stage parasitemia following treatment (10,19), explicitly does not aim to present this measure as a proxy for parasite clearance half-lives or direct evidence of reduced susceptibility of parasites to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At present, artemisinin derivatives retain excellent e cacy throughout Africa despite reports of decreased sensitivity to some of its partner drugs (2). Whilst recent antimalarial e cacy trials in Africa have shown overwhelmingly high treatment success after ACT (≥ 95%) (2), parasites may persist shortly after initiation of treatment (3). Though this parasite persistence may not necessarily re ect drug resistance, which also depends on initial parasite density, host immunity, and drug absorption (4,5), it is important to better understand what parasite populations persist and whether parasite persistence has consequences for later recrudescence (5).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst repeated assessments of parasite density shortly after initiation of treatment provide the most conclusive evidence on (changes in) parasite responsiveness [18], alternative metrics are used to compare the early effects of antimalarials. These include the proportion of individuals with residual parasitemia by microscopy [19] or PCR [4,8] or the concentration of the histidine rich protein-2 parasite antigen [20]. The current study, examining the kinetics of mRNA transcripts indicative of ring-stage parasitemia following treatment [11,21], explicitly does not aim to present this measure as a proxy for parasite clearance half-lives or evidence of reduced susceptibility of parasites to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The current study, examining the kinetics of mRNA transcripts indicative of ring-stage parasitemia following treatment [11,21], explicitly does not aim to present this measure as a proxy for parasite clearance half-lives or evidence of reduced susceptibility of parasites to treatment. A recent study from Mali that was speci cally designed to assess parasite clearance half-lives following artesunate monotherapy observed indications for delayed clearance in one setting [4], highlighting the need for monitoring of (early) parasite clearance following ACTs. Here, the aim was to examine a previously reported phenomenon of persisting sbp1 ring-stage transcripts following ACT treatment in more detail [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation